2021
DOI: 10.1186/s42358-021-00202-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the flare of systemic lupus erythematosus and its influence on prognosis: a single-center retrospective analysis

Abstract: Objectives To explore the risk factors for systemic lupus erythematosus (SLE) flare and their impact on prognosis. Methods The clinical characteristics, laboratory results, and treatment plans of 121 patients with SLE flare were retrospectively analyzed. Ninety-eight SLE outpatients with sustained remission during the same period were selected as controls. Logistic multivariate regression analysis was employed to screen for risk factors for SLE fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…However, previous studies investigating the risk factors of SLE flares did not evaluate the presence of anti-ENA Abs as a potential risk factor 24 30 . One recent study evaluated factors including autoantibody profile for association with the risk of SLE flares 31 but the known potential confounders such as age, sex, ethnicity, complements, renal involvement, disease activity, and use of hydroxychloroquine and immunosuppressants were not adjusted in that study 31 . In the present study, we used multivariable analysis to adjust for potential confounders (ethnicity was not adjusted because all patients included in our study were Korean).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies investigating the risk factors of SLE flares did not evaluate the presence of anti-ENA Abs as a potential risk factor 24 30 . One recent study evaluated factors including autoantibody profile for association with the risk of SLE flares 31 but the known potential confounders such as age, sex, ethnicity, complements, renal involvement, disease activity, and use of hydroxychloroquine and immunosuppressants were not adjusted in that study 31 . In the present study, we used multivariable analysis to adjust for potential confounders (ethnicity was not adjusted because all patients included in our study were Korean).…”
Section: Discussionmentioning
confidence: 99%
“…Providers must balance risk of flare versus risk of infection and other detrimental side effects and/or toxicities from lupus treatments (36). Of interest, one of the most prominently published risks of disease flare is lack of treatment compliance (36,37,(39)(40)(41). With the availability of hydroxychloroquine level testing and other digital and health coach resources (41,42), compliance monitoring may be a beneficial early intervention without escalating treatment, particularly for those patients with a positive FRI-11 below 76% threshold probability of imminent flare.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with relapse in patients with SLE have been reported in many studies, including the increased anti-double-stranded deoxyribonucleic acid, B lymphocyte stimulator, renal organ involvement, deficiency of hydroxychloroquine, premature discontinuation, and poor compliance [ 22 , 33 - 35 ]. Consistent with the factors above, we found that patients with LN had a higher risk associated with relapse, among which 49.1% (55/112) of the patients self-discontinued the treatment.…”
Section: Discussionmentioning
confidence: 99%